2006
DOI: 10.1375/brim.7.2.119
|View full text |Cite
|
Sign up to set email alerts
|

The Evidence Base of Neuropsychological Rehabilitation in Acquired Brain Impairment (ABI): How Good is the Research?

Abstract: In the context of evidence-based clinical practice (EBCP), the reliability of empirical data is largely determined by the methodological quality of research design. PsycBITE™ (Psychological Database of Brain Impairment Treatment Efficacy) is a web-based database listing all published, empirical reports on the effectiveness of nonpharmacological interventions for the psychological consequences of acquired brain impairment (ABI). The aim of this study was to survey the listings of PsycBITE™ and examine the metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…In addition, methodological issues reported in this EBSR and by others who have analyzed the methodological quality of ABI research (e.g., Perdices et al, 2006;Togher et al, 2009) should also be addressed. Findings from those types of studies will provide specific information about telepractice equivalence; however, questions such as "Which patients are most likely to benefit from telepractice?"…”
Section: Telepractice Equivalencementioning
confidence: 99%
“…In addition, methodological issues reported in this EBSR and by others who have analyzed the methodological quality of ABI research (e.g., Perdices et al, 2006;Togher et al, 2009) should also be addressed. Findings from those types of studies will provide specific information about telepractice equivalence; however, questions such as "Which patients are most likely to benefit from telepractice?"…”
Section: Telepractice Equivalencementioning
confidence: 99%
“…As a result, an ethical dilemma is created when funding sources use these conclusions to deny services. In 2006, Perdices et al [41] conducted a review of 1298 empirical studies indexed in a web-based resource for brain injury research called PsycBITE TM . They found that the largest proportion of rehabilitation studies were single subject design (39%), followed by case series (22%), randomized control trials (21%), non-randomized control trials (11%) and systematic reviews (7%).…”
Section: Other Types Of Evidence In Abi Rehabilitation Research: Beyomentioning
confidence: 99%
“…Single Subject Design (SSD) tends to be the predominant model of intervention research for this pop-ulation, not because large randomized control studies are a novel concept in rehabilitation but because the complexities and interplay of human communication, cognition, emotion and behaviour, ABI, and individual circumstances combine to make single subject design more applicable to a wider variety of treatment circumstances [28,41,63]. Perdices et al [41] presented the advantages of single subject design studies and asserted that sophisticated (experimental) SSD's incorporating, among other things, multiple baselines across subjects, as well as randomization of the order of active treatment phases, can potentially provide a level of evidence comparable to that of RCT's.…”
Section: Other Types Of Evidence In Abi Rehabilitation Research: Beyomentioning
confidence: 99%
See 1 more Smart Citation
“…The database currently contains almost 2,000 records meeting selection criteria and is continually updated. All types of research methodology are included systematic reviews, clinical trials, case series and single case experimental designs, and a review of the contents of the database is provided in Perdices et al 2006 . Reports are rated for methodological quality and results of searches are ranked in order of methodological design and methodological quality not alphabetically by author, as occurs with other generic databases .…”
Section: Specific Therapy Programs For Neuropsychological and Social mentioning
confidence: 99%